Understanding tilapia mortalities and fish health management in Lake Volta: a systematic approach - Zornu, Jacob; Tavornpanich, Saraya; Brun, Edgar; van Zwieten, Paul A. M.; van de Leemput, Ingrid; Appenteng, Patrick; Anchirinah, Janet; Cudjoe, Kofitsyo S. (Frontiers in Sustainable Food Systems, 2023)
Lake Volta is a multiuse environment facing various stressors that can affect fish health. In 2018, emerging reports of mortalities among farmed tilapia in Lake Volta were primarily attributed to pathogenic risks. Therefore, this study applied a systemic approach to further investigate the risk factors of tilapia mortalities. The study also examined the management practices deployed to protect fish health and to ensure sustainable lake exploitation. Twenty-six participants were engaged through semi-structured interviews to answer questions on farm information, mortality risk factors, and fish health and lake management practices. Subsequently, the interview data was analysed using the established models of causation web and Social-Ecological System to explain the practical implications of the findings. The findings suggest that the risk factors of tilapia mortalities and diseases in Lake Volta is a combination of pathogens and non-infectious factors mediated by weak enforcement. The pathogens are Streptococcus agalactiae and Infectious Spleen and Kidney Necrosis Virus, which have been confirmed in literature. The non-infectious factors encompass varied human activities that require quantitative investigations to access their roles in deteriorating lake water quality and influencing fish mortalities. Fish health management practices comprised phytotherapy using neem tree leaves, vaccination, heat shock treatment, biological controls, and best husbandry practices. Lake management involves creating a waterfront buffer of 85.34 m, surveillance, and executing the framework guiding aquaculture development on the Lake. The findings are suggestive of complementary quantitative studies to augment the qualitative evidence from this study. This can disclose precise tilapia disease and mortality risk factors and inform targeted policy directives, as well as effective remedial strategies.